Melanin levels in relation to vitamin D among first-generation immigrants from different ethnic groups and origins: A comparative national Canadian cross-sectional study - Yousef, Said; Papadimitropoulos, Manny; Faris, MoezAlIslam; Hasan, Hayder; Hossain, Alomgir; Colman, Ian; Manuel, Douglas; Wells, George A. (Frontiers in Medicine, 2023)
Introduction: Immigrants to Western countries tend to have darker skin than native-born populations. We examined the relationship between skin melanin and serum vitamin D (S-25(OH)D) levels and explored whether melanin levels explained S-25(OH)D variations between immigrants and native-born Canadians. This study offers novel findings as no such study has been conducted. Methods: We used a national cross-sectional population-based design with data from the Canadian Health Measures Survey. Skin melanin levels among first-generation immigrants based on their ethnicity and origin/country of birth were compared with white and native-born populations. We assessed the association between S-25(OH)D and melanin after adjusting for independent variables related to S-25(OH)D, melanin level and immigration status. Results: Of 11,579 participants, 21.9% were immigrants aged 3–79 years (mean age 39.23 years). Compared with non-immigrants, immigrants had lower S-25(OH)D levels (mean: 51.23 vs. 62.72; 95%CI: 8.37, 14.62; P<0.001) but higher melanin levels (mean [SE]: 17.08 [0.25] vs. 16.29 [0.29]; 95%CI: −1.29, −0.281; P=0.004). Melanin did not differ by length of stay in Canada but was weakly positively correlated (r=0.088, P<0.001) with S-25(OH)D. Sex (male), age (≥18 years), summer/fall seasons, sunlight exposure, sunscreen non-use, smoking, and alcohol consumption were associated with higher melanin levels, whereas indoor tanning use was not. Conclusion: Skin melanin levels were associated with sociodemographic and behavioural characteristics. Immigrants had higher melanin levels, but melanin did not differ by length of stay in Canada. The weak positive correlation between melanin and S-25(OH)D suggested confounding factors may impact the relationship between melanin levels, S-25(OH)D, and immigration status.